2020
DOI: 10.1111/acps.13158
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic liability for schizophrenia and childhood adversity influences daily‐life emotion dysregulation and psychosis proneness

Abstract: liability for schizophrenia and childhood adversity influences daily-life emotion dysregulation and psychosis proneness.Objective: To test whether polygenic risk score for schizophrenia (PRS-S) interacts with childhood adversity and daily-life stressors to influence momentary mental state domains (negative affect, positive affect, and subtle psychosis expression) and stress-sensitivity measures. Methods: The data were retrieved from a general population twin cohort including 593 adolescents and young adults. C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 78 publications
(82 reference statements)
3
37
1
Order By: Relevance
“…A recent study from the 1966 Northern Finland Birth Cohort showed that high birth weight, a risk factor for familial schizophrenia in this cohort, increased the association between PRS-SCZ and social anhedonia, suggesting a gene–environment interaction (Liuhanen et al ., 2018). Similarly, a study conducted in a general population twin cohort demonstrated that while PRS-SCZ was not independently associated with affective dysregulation and psychosis proneness, PRS-SCZ increased sensitivity to the effect of childhood adversities on affective dysregulation and psychosis proneness (Pries et al ., 2020 a ). Although not a direct test of gene–environment interaction, a study of healthy young males assessed during their compulsory military service showed that there was a negative association between PRS-SCZ and positive schizotypy at military induction (stressful condition) but not at follow-up, providing further support for the key role of environment in the phenotypic expression of schizotypy traits (Hatzimanolis et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from the 1966 Northern Finland Birth Cohort showed that high birth weight, a risk factor for familial schizophrenia in this cohort, increased the association between PRS-SCZ and social anhedonia, suggesting a gene–environment interaction (Liuhanen et al ., 2018). Similarly, a study conducted in a general population twin cohort demonstrated that while PRS-SCZ was not independently associated with affective dysregulation and psychosis proneness, PRS-SCZ increased sensitivity to the effect of childhood adversities on affective dysregulation and psychosis proneness (Pries et al ., 2020 a ). Although not a direct test of gene–environment interaction, a study of healthy young males assessed during their compulsory military service showed that there was a negative association between PRS-SCZ and positive schizotypy at military induction (stressful condition) but not at follow-up, providing further support for the key role of environment in the phenotypic expression of schizotypy traits (Hatzimanolis et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For our primary analyses, we used the P -threshold of < .05, as this threshold explained most variation in the phenotype in the Psychiatric Genomics Consortium analysis 41 and was previously shown to perform well for the current phenotype of SF-36 mental health. 42 For details on the genotyping, see the supplementary material . Statistical analyses were adjusted for 3 principal components.…”
Section: Methodsmentioning
confidence: 99%
“…24,42 We used a composite stress measure (row mean) consisting of items assessing eventrelated, activity-related and social stress to avoid multiple testing. 70,71 Event-related stress: Participants were asked to rate the most important event since the last beep on a 7-point Likert scale ranging from -3 (very unpleasant) to 3 (very pleasant). We recoded this item so that higher ratings indicate higher levels of stress (-3 recoded as 7 and 3 recoded as 1).…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies we aggregated event-related, activity-related and social stress to a composite stress measure for each beep to reduce multiple testing. 70,71 Still, type I error should be taken into account when interpreting the results.…”
Section: Methodological Considerations/ Limitationsmentioning
confidence: 99%